Surgical approach affecting long-term urinary continence status after robot-assisted laparoscopic prostatectomy prospectively evaluated using self-reported functional status (Expanded Prostate Cancer Index Composite, EPIC-26) - Mathias Reichert; Arne Strauß; Joost Wilhelm Voß; Hans Christoph von Knobloch; Hannah Maria Neuenhofer; Annemarie Uhlig; Lutz Trojan; Mirjam Naomi Mohr (Current Urology)
Abstract. Purpose. The aim of the study was to examine the influence of the surgical approach for robot-assisted laparoscopic prostatectomy (RALP) on long-term urinary continence status in the era of self-reported functional status measures using the Expanded Prostate Cancer Index Composite 26. Materials and methods. This is a prospective evaluation of 232 patients undergoing RALP between September, 2019 and September, 2020. Urinary continence status and postoperative incontinence (pad usage) were evaluated 12 months after RALP using Expanded Prostate Cancer Index Composite 26 questionnaires. Patients were categorized according to their surgical approach and outcome into the following groups: successful nerve sparing (NS), primarily without nerve sparing (prim. NNS), and no nerve sparing by secondary resection (NNS by SR). The median levels of their questionnaire outcomes were evaluated and compared using the Wilcoxon rank sum test with continuity correction. Results. Urinary continence status 12 months after RALP differed significantly between the NS and prim. NNS (p = 0.0071) and the NS and NNS by SR (p = 0.0076) groups. There was no significant difference between the prim. NNS and NNS by SR (p = 0.53) groups. Pad usage 12 months after RALP had no significant difference with regard to SR of the neurovascular bundle (p = 0.14). Conclusions. Patient-reported outcomes of long-term urinary continence status seem to show no difference in postoperative continence, regardless of whether a non–nerve-sparing result was planned or reached through SR. Instead, preservation of neurovascular bundle seems to lead to better long-term continence rates.